THE EFFECT OF SONIC HEDGEHOG IN PROTECTIVE FROM OX-LDL-INDUCED ENDOTHELIAL APOPTOSIS. (April 2021) - Xue, Yan; Huang, Huashan; Yu, Huizhen; Lin, Liang; Chen, Junming; Zhu, Pengli
Abstract: Objective: Sonic hedgehog (Shh) is of pivotal importance to embryonic and adult blood vessels development and homeostasis. The aim of our study is to further investigate the role of Shh in oxidized low-density lipoprotein (ox-LDL) medicated endothelium damage and apoptosis. Design and method: Western immunoblots were assessed to the protein expression of hedgehog component, Bcl-2 and caspase 3 in human umbilical vein endothelial cells (HUVECs) induced by ox-LDL. The flow cytometry of FITC Annexin V/PI and caspase 3 activity kit were used to determine cell apoptosis. Results: Our study found that ox-LDL can induce the apoptosis of HUVECs in vitro and the protein expression of Shh was down regulated. Furthermore, retreatment with rShh or transfection with phShh can increase the anti-apoptosis protein Bcl-2 expression and decrease cell apoptosis. These protection effects of rShh or phShh could be abolished by cyclopamine, which is a hedgehog signaling inhibitor. Moreover, we performed co-immunoprecipitation assay to demonstrate that Shh interacted with nuclear factor-kB (NF-kB)p65 in HUVECs. Additionally, ox-LDL upregulated the phosphorylation of NF-kBp65 and inhibitor-kB -a (IkBa), and these effects lessened notably after rShh and phShh treatment. Conclusions: Our findings suggest that Shh plays an important protective role in alleviating ox-LDL-mediated endothelial apoptosis by inhibiting NF-kB signaling pathway and controlling mitochondrial signaling.